THE EFFECT OF TYPE OF PEELING AGENT, COOKING TIME AND MOISTURE CONTENT ON GIANT WHITE CORN (Zea mays) FRIED SNACK QUALITY - Boluarte Alarcón, Geimy I. (2018)
In order to improve the organoleptic properties of giant corn fried snack, the effects of chemical peeling agent type (CaOH or NaOH), immersion in peeling solution, cooking time, and grain moisture content before frying, were studied. NaOH was found to be more effective than CaOH as a peeling agent of corn. Nixtamalization flavor was best developed and a lighter snack color was obtained when corn grains were immersed in the peeling solution of NaOH for 6 h. A longer cooking time (0, 8, 16 min) yielded a larger grain expansion. By adjusting grain moisture content (before frying) by drying, the texture of the snack could be controlled. High moisture contents, > 42 % (w.b.) produced crunchy but hard-textured snacks; whereas, low moisture contents, < 26 % (w.b.) gave soft but dry-textured snacks. Therefore, in order to obtain crunchy but soft snacks, moisture content must be adjusted to approximately 32 % (w.b.).